Variación mineral en dos gramíneas de tierra fría. - Laredo Covarrubias, Max A.; Ánzola Vásquez, Héctor J.; Ardila G, Armando (Instituto Colombiano Agropecuario - ICA, 2018)
Ganado de leche-Ganadería leche